EFFECT OF DIFFERENT RATES OF COW DUNG ON YIELD INDCES OF GROUNDNUT IN ABRAKA, DELTA STATE, NIGERIA - Enujeke, E. C.; Anwuli-Okoh, L. A. (FUDMA JOURNAL OF SCIENCES, 2023)
This experiment was conducted in 2022 and repeated during 2023 farming season at the Teaching and Research Farm of Delta State University, Abraka to assess the response of selected varieties of groundnut to different rates of cow dung in Abraka, Delta State. It was a 5 x 2 factorial experiment carried out in randomized complete block design with three replications. The rates of cow dung in tha-1 were 0, 5, 10, 15, and 20, while the varieties were Samnut-21 and Samnut-22. After analysis of variances and means separation with Duncan Multiple Range Test (DMRT) of the data collected on yield indices of groundnut, the results indicated that Samnut-21 was outstanding in all the parameters assessed. Manure application rate of 20tha-1 gave the highest values with respect to yield of groundnut in Abraka ecology. It was therefore recommended that 20tha-1 of cow dung be applied to Samnut-21 for increased yield of groundnut in Abraka, Delta State, Nigeria.